Externalities, Communication and the Allocation of Decision Rights - Helmut Bester (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper views authority as the right to undertake decisions that impose externalities on other members of the organization. When only decision rights can be contractually assigned to one of the organization's stakeholders, the optimal assignment minimizes the resulting inefficiencies by giving control rights to the party with the highest stake in the organization's decisions. Under asymmetric information, the efficient allocation of authority depends on the communication of private information. In the case of multiple decision areas, divided control rights may enhance organizational efficiency unless there exist complementarities between different decisions.
urn:nbn:de:bvb:19-epub-13481-0
Keywords: D23; D82; L22; P14; 330; Authority; Decision Rights; Externalities; Incomplete Contracts